VD_FINDINFO MP / 2011 / 6 vom 11. Februar 2011 - VD Tribunal cantonal (2011)
MESURE PROVISIONNELLE, CONCURRENCE DÉLOYALE, PUBLICITÉ COMPARATIVE | 2 LCD, 3 al. 1 let. e LCD, 9 al. 2 LCD, 261 CPC (CH), 262 CPC (CH), 263 CPC (CH), 264 CPC (CH)